(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The article examines English proverbs that include proper names to convey lessons or ideas quickly and effectively. It explains how these proverbs have both a literal meaning and a deeper, symbolic meaning, often drawn from cultural or historical contexts. The analysis highlights how these proverbs use memorable language to pass on wisdom, reflect societal values, and facilitate communication.